Designing a Microcontroller-Based Attendance System for Lecturers and Employees Using Rifd and MYSQL Database at AMIK Medicom - Febrian Sihombing; Veriandus lumbanbatu; Alditia preangin angin (Journal Majelis Paspama, 2025)
An effective and efficient attendance system is an important requirement for educational institutions and organizations. Manual attendance systems that are still in use often cause various problems, such as recording errors, data loss, and time-consuming processes. This study aims to design and develop a microcontroller-based attendance system for lecturers and employees using RFID technology integrated with a MySQL database at AMIK Medicom. The research methodology uses a waterfall approach that includes analysis, design, implementation, and testing stages. The hardware used includes an ESP32 microcontroller, RFID sensor, buzzer, and RFID identity card, while the software consists of Arduino IDE, XAMPP, and MySQL database. The implementation results show that the attendance system is capable of detecting RFID cards properly, automatically recording attendance in the database, and providing real-time notifications through the Telegram application. This system has been proven to improve the efficiency, accuracy, and security of the attendance process compared to manual methods.